ISLAM DI NUSANTARA; MENYINGKAP TABIR NILAI RELIGIUSITAS SUFISTIK DALAM PANDANGAN SYED MUHAMMAD NAQUIB AL-ATTAS (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2019)
Abstract This paper explore Islam Nusantara (Islam of the Archipelago) as a regional study aimed to formulate a theory that can seek the type, form, and pattern of Islam in the Indonesian archipelago (Nusantara). The ultimate purpose was to create a unique characteristic of the Indonesian society’s Islamic life.According to Syed Muhammad Naquib Al-Attas, Islam Nusantara is a type of Islam which root came from the Sufism concept of wujūd (Unity of Being). Findings showed that Islam Nusantara in the perspective of Al-Attas has had its own characteristics: the Islam was based on Sufism as it was the original face of the Indonesian society’s Islamic life. Al-Attas argued that Islam Nusantara did not merely come from the thin layer of previous civilizations rather it had brought with its modernization by which it later changed the Indonesian society’s view from the aesthetic and magic to the metaphysical, more rational worldview. In conclusion, it can be understood that IslamNusantara is a Sufism in Islam which based on the real philosophy of Islam.